EFFECT OF (CLAY & SILT) FRACTIONS AND CARBONATES MINERALS ON PEDOGENIC DISTRIBUTION OF MANGANESE EXTRACTED BY DIFFERENT METHODS - Adel Mawlood Salih; Mohammed Tahir Said Khalil (Mesopotamia Journal of Agriculture)
Eight soil profiles were chosen, representing three locations in Nineveh governorate (Al-Fadhlia, Kara-Tapa, and Al-Hamdania). The study was aimed for better understanding the effect of (caly & silt) fraction and carbonates minerals on distribution of manganese extracted by three selective dissolution methods [DTPA , Glacial acetic acid (GAc.) and DCB] . The results indicated that the DTPA extractable manganese showed a similar behavior in the pedogenic distribution with the highest concentration in surface horizons between 2.5 -5.6 mg. kg-1, but concentrations decreased with depth . However GAc. extractable manganese ranged 25.6-72.2 mg. kg-1 , while DCB extracted between 10-58 mg. kg-1. Statistical analysis showed a significant relation between (clay & silt) fraction of soil and DTPA extractable manganese in two locations (Al-Fadhlia and Al-Hamdania), while GAc and DCB extractable manganese has a significant relationship with (clay & silt) fraction in Kara-Tapa and Al-Hamdania Locations respectively. Carbonateminerals has a significant effect on distribution of extractable manganese only in Al-Hamdania area regardless of the extracting method